Leaf and seed yield of nagauri methi (Trigonella corniculata) as influenced by seed rates and nitrogen levels - MEHRIYA, MOTILAL; SHUKLA, UMA NATH; UPADHYAY, P K; BORANA, HITESH; SINGH, RAJIV KUMAR (The Indian Journal of Agricultural Sciences, 2021)
The study concluded that fresh weight of leaf (cutting wise), total fresh and dry weight of leaf, and seed yield and viable economic advantages in cultivation of nagauri methi were obtained significantly under the treatment combination of 100 kg/ha seed rate and 45 kg N/ha. It was further summarized that combination of 100 kg/ha seed rate and 45 kg N/ha had produced significantly higher quantity of dry leaf and seed yield as well as better monetary return in terms of gross return and net return resulted in higher B: C ratio under Arid Zone of Western Rajasthan.